Bioregenerative Life Support Systems in Space Research - Häder, Donat-Peter; Braun, Markus; Hemmersbach, Ruth (Gravitational Biology I - Gravity Sensing and Graviorientation in Microorganisms and Plants, 2018)
For manned long-term missions e.g. to Mars, large amounts of food and oxygen are required to sustain the astronauts during the months-or year-long travel in space but resources are very limited. Water is already routinely recycled on the ISS. In order to solve the problem of limited food and oxygen resources, bioregenerative life support systems are envisioned with closed nutrient and gas loops. Several ecological model systems varying in the degree of complexity have already been investigated on ground and tested on shorter space flights. Photosynthetic organisms such as flagellates or higher plants produce oxygen when light is available. Simultaneously they take up the carbon dioxide exhaled by the astronauts or other consumers. Urea and ammonia can be detoxified by bacteria. Insertion of a component of primary consumers such as ciliates could be used to produce fish for human consumption.
CRIS-Team WoS Importer:2019-04-18